High Pressure (Eclogite Facies) Metamorphism in the Indian Plate, NW Himalaya, Pakistan - Spencer, D.A.; Ramsay, J.G.; Spencer-Cervato, C.; Pognante, U.; Chaudhry, M.N.; Ghazanfar, M. (Journal of Himalayan Earth Sciences, 1990)
A zone of high pressure (eclogite facies) metamorphism, characterized by eclogites with an assemblage of omphacite - garnet - quartz - rutile ± phengite, has been recognized in the higher Himalaya in the Indian Plate of NE Pakistan. This suggests that the Upper Kaghan Nappe is the deepest derived part of the Indian Plate to have been subducted and subsequently uplifted along the whole length of the Himalaya. Mineral chemistry by microprobe analysis suggests that the eclogites formed at temperatures of 650±50oC and pressures of 13-18 kbar, suggesting depth of eclogite formation at 60 km. The eclogites show an incipient decompressional re-equilibration which probably occurred at decreasing temperatures.